Identification of Linear B-Cell Epitopes on Hemagglutinin Protein of Canine Distemper Virus Using Two Monoclonal Antibodies - Shi, Pengfei; Cao, Zhigang; Cheng, Yuening; Cheng, Shipeng; Yi, Li (Frontiers in Veterinary Science, 2020)
Canine distemper virus belongs to the Morbillivirus genus of the Paramyxoviridae family, which causes conservation threat to the domestic dogs and fur-animal industry. Hemagglutinin protein is the major membrane protein as the key molecular factor in CDV tropism, also known as inducing host to produce neutralizing antibodies. However, the immunogenicity of CDV hemagglutinin protein has not been investigated clearly. In this study, we produced two monoclonal antibodies 1A5 and 2B8 against the H protein of CDV strain PS. A series of partially overlapping synthesized peptides, covered the hemagglutinin protein (aa50-204), were screened to identify linear epitopes recognized by 1A5 and 2B8 MAbs. Afterwards, 120QKTNFFNPNREFDFR134 (F8) and 178ARGDIFPPY186 (F14-1) are minimal linear epitopes recognized by 1A5 and 2B8 MAbs, respectively. Further investigation revealed that mAb 1A5 can recognize CDV-PS strain and CDV-R strain, but can not react with CDV-3 strain. Meanwhile, CDV-PS, CDV-R and CDV-3 strain can be recognized by mAb 2B8, because 120QKTNFFNPNREFDFR134 is conserved in these strains. The epitopes 120QKTNFFNPNREFDFR134 and 178ARGDIFPPY186 localized at the surface of hemagglutinin protein in 3D structure. CDV-infected dog serum can also recognize the identified B cell epitopes. In brief, the specific epitopes of this study may provide the development of potential diagnostic methods.